KATA SAPAAN KEKERABATAN MASYARAKAT JAWA DI DESA KERAMAS KECAMATAN PARIT CULUM I KABUPATEN TANJUNG JABUNG TIMUR (KAJIAN SOSIOPRAGMATIK) - Aprillia Ningsih; Sainil Amral; Supriyati Supriyati (Universitas Batanghari, 2025)
This study aims to describe the form and function of kinship greetings in Javanese society in Keramas Village, Parit Culum 1 District, East Tanjung Jabung Regency. The desire to conduct this research is to preserve the regional language where the researcher lives and at the same time complete the final assignment in the field of science that the researcher is studying. To carry out this research, the researcher used a qualitative descriptive research type. To obtain research data, the researcher obtained it from 6 informants. The data from these informants was then analyzed by the researcher using the theory of Suharyanto (2008: 17) and Biber (2020: 47) with this type of research the researcher can describe the form and function of kinship greetings both from blood relations and marriage ties used in this village. The results of this study indicate that there are 34 forms of blood relations greetings and 16 kinship greetings. Meanwhile, the function of greeting words for blood relations is to mark the interlocutor 18, and to maintain social relations between speakers 14. Furthermore, the function of greeting words for marriage ties is to greet 20, and to mention